Noise exposure assessment of non-coal mining workers in four provinces of China - Wang, Xin; Kang, Ning; Dong, Yiwen; Liu, Kai; Ning, Kang; Bian, Hongying; Han, Feng; Chen, Yongqing; Ye, Meng (Frontiers in Public Health, 2023)
Objective: This study aimed to understand the noise exposure of non-coal mines in China to take appropriate controls to protect workers’ health. Methods: An assessment of non-coal miners’ noise exposures were conducted in 4 provinces in China. Individual noise exposure level (LEX.8h) was measured, and the survey on the hearing protector devices (HPD) equipment was administered. Results: 423 noise dosimeter measurements were obtained, including drilling, blasting, ore drawing, transportation, winching, crushing, screening and ball milling, and auxiliary (air pressure, pump, and maintenance). 31.9% of the individual noise levels (LEX.8h) exceeded 85dB(A), and the median dosages of non-coal miners with high noise exposure were: excavation workers-89.1dB(A), mill operators-88.7dB(A), crusher operators-87. 0dB(A). The noise dose of underground mine workers is higher than that of surface mine workers (P<0.001). 53.7% of non-coal mine enterprises are not equipped with HPD for workers, mainly small and micro enterprises. Conclusions: High levels of hazardous noise exposure are typical in non-coal mines. Noise exposure data can help to develop more feasible noise controls.